The Long Noncoding RNA 150Rik Promotes Mesangial Cell Proliferation via miR-451/IGF1R/p38 MAPK Signaling in Diabetic Nephropathy - Yajuan Zhang; Yan Sun; Rui Peng; Handeng Liu; Weihao He; Luyu Zhang; Huimin Peng; Zheng Zhang (Cellular Physiology and Biochemistry, 2018)
Background/Aims: Diabetic nephropathy (DN) as the primary cause of end-stage kidney disease is a common complication of diabetes. However, the initiating molecular events triggering DN are unknown. Recently, long noncoding RNAs (lncRNAs) have been shown to play important roles in DN. Methods: The expression level of lncRNA 1500026H17Rik (150Rik for short) was measured by qRT-PCR (quantitative real-time PCR). Cell proliferation ability was detected by 5-Ethynyl-2’-deoxyuridine (EdU). The relationship between 150Rik and microRNA 451 (miR-451) was examined by luciferase assay and RNA immunoprecipitation (RIP) assay. Finally, the effect of 150Rik on cell proliferation through the miR-451/insulin-like growth factor 1 receptor (IGF1R)/mitogen-activated protein kinases (p38MAPK) pathway was detected by EdU, flow cytometry analysis, western blot. Results: We found that 150Rik, an evolutionarily conserved lncRNA, was significantly upregulated in renal tissue of db/db DN mice and in mesangial cells (MCs) cultured under a high glucose condition. Further, overexpression or knockdown of 150Rik was found to regulate cell proliferation in MCs. Moreover, 150Rik was found to interact with miR-451 in both a direct and argonaute-2 (Ago2)-dependent manner. Results also revealed that overexpression of 150Rik inhibited cell proliferation through the miR-451/IGF1R/p38MAPK pathway in MCs under the high glucose condition, while knockdown of 150Rik increased cell proliferation via the miR-451/IGF1R/p38MAPK pathway. Conclusion: Taken together, these results provide new insight into the association between 150Rik and the miR-451/IGF1R/p38MAPK signaling pathway during DN progression.